2006
DOI: 10.1186/1471-2180-6-42
|View full text |Cite
|
Sign up to set email alerts
|

Identification and properties of proteases from an Acanthamoeba isolate capable of producing granulomatous encephalitis

Abstract: Background: Granulomatous amoebic encephalitis due to Acanthamoeba is often a fatal human disease. However, the pathogenesis and pathophysiology of Acanthamoeba encephalitis remain unclear. In this study, the role of extracellular Acanthamoeba proteases in central nervous system pathogenesis and pathophysiology was examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 26 publications
0
25
0
1
Order By: Relevance
“…The initial binding of Acanthamoeba to the surface of host cells interferes with the host intracellular signalling pathways. Several studies have shown that Acanthamoeba induces apoptosis in host cells (Alizadeh et al , 1994; Sissons et al , 2005a). Apoptosis, or programmed cell death, is known to be dependent on the host cell's own signalling pathways, involving Ca 2+ responses (Taylor et al , 1995).…”
Section: Pathogenesismentioning
confidence: 99%
“…The initial binding of Acanthamoeba to the surface of host cells interferes with the host intracellular signalling pathways. Several studies have shown that Acanthamoeba induces apoptosis in host cells (Alizadeh et al , 1994; Sissons et al , 2005a). Apoptosis, or programmed cell death, is known to be dependent on the host cell's own signalling pathways, involving Ca 2+ responses (Taylor et al , 1995).…”
Section: Pathogenesismentioning
confidence: 99%
“…Various factors affect the prevalence of TB. Previous studies have found that the prevalence of TB is associated with individual differences, such as genetic susceptibility [ 4 ], sex [ 5 ], education [ 6 ], race [ 7 , 8 ], migration [ 9 ], drinking alcohol [ 10 ], smoking [ 11 ], and related diseases [ 12 , 13 , 14 ]. Additionally, at the ecological level, geographic, climatic and socio-economic factors also impact TB prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…These factors include elevation [ 15 ], climate [ 16 ], air pollution [ 11 ], the national economic level [ 17 ], unemployment rate [ 10 ], poverty [ 18 ], and social instability [ 19 ]. Compared to individual studies [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], ecological studies on TB prevalence are relatively insufficient [ 10 , 11 , 15 , 16 , 17 , 18 , 19 ], especially in China. These ecological studies primarily investigated the effects of certain factors on TB prevalence and did not systematically address the comprehensive effects of these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this result, type I toxin TisB was directly linked with persistence as absence of tisAB/istR locus led to significant reduction in ciprofloxacin induced persistence [ 28 ]. Furthermore, expression of TA modules (RelBE, MazEF, DinJYafQ, MqsR, YoeB) were induced in a transcriptome study performed with isolated E. coli persister cells [ 29 ].…”
Section: Introductionmentioning
confidence: 99%